Influence of property rights and collective action on the choice of technology - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
The technologies people use play a fundamental role in shaping the efficiency, equity, and environmental sustainability of natural resource management (NRM). However, improved agricultural and natural resource technologies are of little value unless they are judged to be appropriate by farmers and subsequently adopted. There are many factors constraining farmers' Influence of Property Rights and technology choices, but the lack of secure property rights has been commonly identified as an important barrier to adoption, particularly for longer-term investments in tree crops and improvements to natural resources.